Glass Hardness Modification by Means of Ion Implantation: Electronic Doping versus Surface Composition Effect. Issue 7 (2nd May 2019) - Idé, Julien; Cornil, David; Jacques, Amory; Navet, Benjamine; Boulanger, Pierre; Ventelon, Lionel; Lazzaroni, Roberto; Beljonne, David; Cornil, Jérôme
Abstract: Critical load measurements point to an improvement in the hardness of a soda–lime glass upon nitrogen implantation. In order to determine whether this improvement originates from electronic doping or surface composition changes induced by ion implantation, a theoretical approach using quantum‐chemical and force‐field methods combined with X‐ray photoelectron spectroscopy is performed. The results indicate that neither an electronic effect nor a lattice distortion appear to be the primary cause of the hardness improvement. It is rather a change in the surface composition leading to a more densely cross‐linked and stiffer silica network at the top surface of the glass which is at the origin of this improvement. Abstract : The origin of the improvement in the hardness of a soda–lime glass upon nitrogen implantation is investigated by a theoretical approach combined with X‐ray photoelectron spectroscopy. The results indicate that a change in the surface composition upon ion implantation is the primary cause for this improvement rather than electronic or lattice distortion effects.